Citizen Science in Post-Fukushima Japan: The Gendered Scientization of Radiation Measurement. (3rd July 2019) - Kimura, Aya H.
ABSTRACT: After the Fukushima nuclear accident, many laywomen established citizen radiation measuring organizations (CRMOs) to measure the concentration of radioactive materials in food to ensure its safety. These women had diverse motivations. As caretakers, many wanted to protect their families. Others saw it as important to arm themselves with science when the broader social discourse portrayed contamination concerns as irrational and harmful to food producers, and stereotyped women as overreacting due to their scientific illiteracy. Some women also became empowered and productive citizen scientists, influenced by the popular idea of women-in-science. The fluid relationships between scientization and citizens' collective mobilizations make it particularly illuminating to analyze such shifting relationships between activism and science using Gieryn's concept of boundary-work. Women's motivations to participate in CRMOs were closely connected to the expanding scientization—the increasing role of science in defining and prescribing social problems. While they shared many sentiments with anti-nuclear movements, women often performed boundary-work in a way that constructed science as irreconcilable with activism. Many saw activism as threatening the legitimation provided by science: a particularly important issue for women, who were stereotyped and policed as anti-science and irrational after the accident. Activism was also understood as a highly masculinized space incompatible with the feminized caretaker role that many women took on, which initially provided the rationale for their involvement in citizen science. The concept of gendered scientization highlights how the turn to science in dealing with environmental threats might result in gendered opportunities and challenges in collective mobilization by citizens.